2003
DOI: 10.1016/s1476-5586(03)80028-3
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Activation of the Androgen Receptor Downregulates E-Cadherin-Mediated Cell Adhesion and Promotes Apoptosis of Prostatic Cancer Cells

Abstract: Androgen independence is the major cause of endocrine therapy failure in advanced prostate cancer (PC). To examine the effects of human androgen receptor (AR) expression on growth of human PC cells, transfection of full-length AR cDNA in an androgen-insensitive human prostatic adenocarcinoma cell line (DU145) was performed. Transcriptional activity of AR was confirmed by the MMTV luciferase assay and AR expression was assessed by reverse transcriptase polymerase chain reaction, Western blotting, and immunocyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 63 publications
2
17
0
Order By: Relevance
“…1, were separated onto SDS-PAGE and, after blotting, probed with the anti-EAA1 polyclonal antibody. Nightingale et al 2003, Guierini et al 2005, Hatzoglou et al 2005. Inline with our data, it has recently been shown that transfection of AI PC cell lines with the endocytosis protein REPS2 results in inhibition of EGFR internalization and decrease of related signalling (Oosterhoff et al 2005).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…1, were separated onto SDS-PAGE and, after blotting, probed with the anti-EAA1 polyclonal antibody. Nightingale et al 2003, Guierini et al 2005, Hatzoglou et al 2005. Inline with our data, it has recently been shown that transfection of AI PC cell lines with the endocytosis protein REPS2 results in inhibition of EGFR internalization and decrease of related signalling (Oosterhoff et al 2005).…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, it has recently been demonstrated that during PC progression from low grade to high grade and metastatic PC, a selective downregulation of the AR-targeted genes that inhibit proliferation, induce differentiation or mediate apoptosis occurs (Hendriksen et al 2006). Altogether this evidence supports the notion that a correct AR pathway may maintain a more differentiated phenotype of PC, as observed in vitro in androgen-positive PC cell lines (Bonaccorsi et al 2000, 2004a, Cinar et al 2001, Davis et al 2003, Nightingale et al 2003, Guerini et al 2005, Hatzoglou et al 2005 both by regulating genes affecting growth and invasion (Bonaccorsi et al 2000, Hendriksen et al 2006 and by interfering with signal transduction of EGF (Bonaccorsi et al 2004a, Oosterhoff et al 2005; present study).…”
Section: Discussionmentioning
confidence: 76%
“…They are involved in the regulation of the expression of many target genes, which are significant during early stages of fetal folliculogenesis and are critical for reproduction (Nightingale et al 2003). Previously, we demonstrated the presence of ARs in the porcine fetal ovary at different stages of gestation (Burek et al 2007) indicating the possible sites of androgen action.…”
Section: Introductionmentioning
confidence: 76%
“…Whether the activated AR can promote prostate cancer cell migration, still remains unknown. Certain studies have indicated that the activated AR-B can promote prostate cancer cell migration (23,24), although others have shown that androgen derivatives can inhibit this phenomenon (25,26). The AR signal pathway could have diverse effects on the molecules involved in the processes of invasion and metastasis which could lead to positive (the up-regulation of NEP, HSP, DPM3/prostin-1, the down-modulation of the ·6ß4 and ·3ß1 integrins, MMP1, MMP3, MMP7, and ET-1 secretion) and to negative (the upregulation of pro-MMP-2) effects on PC cell invasion.…”
Section: Discussionmentioning
confidence: 99%